DARE Newsletter, Vol. 8, No. 4, Fall 2005 - DARE; Porter, Ruth; Simon, David (Dictionary of American Regional English, 2005)
Contents: "Postcards from Florida: A Fieldworker Reminiscence" by Ruth Porter; "Funding Update" by David Simon; "Notes and Quotes"; "DARE Showcased in Chicago"; "Staff Member Profile: David Nunnery"; "DARE Staff Changes"
Quarterly newsletter of the Dictionary of American Regional English
Keywords: Americanisms; Dictionaries; Lexicography; Regional English; English Language--Dialects--United States; Fieldwork